2022
DOI: 10.1186/s12931-022-01996-w
|View full text |Cite
|
Sign up to set email alerts
|

Impaired AT2 to AT1 cell transition in PM2.5-induced mouse model of chronic obstructive pulmonary disease

Abstract: Background Particular matter 2.5 (PM2.5) is one of the most important air pollutant, and it is positively associated with the development of chronic obstructive pulmonary disease (COPD). However, the precise underlying mechanisms through which PM2.5 promotes the development of COPD remains largely unknown. Methods Mouse alveolar destruction were determined by histological analysis of lung tissues and lung function test. Alveolar type II cells (AT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 62 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…At present, some progress has been made in the relationship between aging, and chronic obstructive pulmonary disease and pulmonary fibrosis [ 48 ]. However, the specific molecular mechanism and functional relationship of aging in the occurrence and the development of chronic obstructive pulmonary disease and pulmonary fibrosis are not completely clear [ 49 ]. Finding these molecular mechanisms and functional relationships may bring hope to cure these diseases [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, some progress has been made in the relationship between aging, and chronic obstructive pulmonary disease and pulmonary fibrosis [ 48 ]. However, the specific molecular mechanism and functional relationship of aging in the occurrence and the development of chronic obstructive pulmonary disease and pulmonary fibrosis are not completely clear [ 49 ]. Finding these molecular mechanisms and functional relationships may bring hope to cure these diseases [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung organoids are already used for different research questions regarding NM toxicity. Readouts including reactive oxygen species (ROS) production, epithelial cell differentiation and regeneration, NP internalization or surfactant production can be assessed easily, and help to elucidate the mechanisms underlying disease progression in the lung after NP exposure [ 66 , 67 , 68 ]. Toxicity testing in organoids is not yet used often, but these examples already show the numerous opportunities with 3D lung cultures.…”
Section: Culture Methods For Nm Hazard Assessmentmentioning
confidence: 99%
“…However, one difficulty still is to imitate the inhalation of NMs. For example, in Yu et al 2022 [ 68 ], the particles to be tested are mixed into the culture medium, which is without a doubt a convenient and high throughput suitable approach for NM exposure, but leads to similar problems regarding the cell delivered dose and the particle–cell interaction as a conventional 2D submerged cell culture does. Nevertheless, 3D organoids are able to respond to stimuli and can recapitulate epithelial cell responses more accurately than 2D culture [ 69 ].…”
Section: Culture Methods For Nm Hazard Assessmentmentioning
confidence: 99%
“… 94 After being exposed to PM2.5, it is observed that there are fewer multilamellar bodies in the Alveolar epithelial type II; cell (AT2) increases mitochondrial swelling, collagen deposition, and pulmonary inflammation. 95 In addition, it can be observed that the dysregulated AT2 cells into AT1 cells in the PM2.5-induced COPD mouse model 96 damage cellular repair mechanisms. Even worse, it has been shown that inflamed bronchial epithelial cells caused by air pollution particles trigger apoptosis, 97 particularly when PM2.5 is injected into those inflamed by cigarettes.…”
Section: Pm25 Induced Pathogenesis In Copdmentioning
confidence: 99%